Community Empowerment in Improving the Economy Through the Development of Charcoal Business in Ketandan Village, Lengkong Subdistrict, Nganjuk District - Umah, Yuli Choirul; Masrifatin, Yuni (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The implementation of the community service program in Ketandan Village takes a work program for assisting the production of Wood Charcoal. The use of wood charcoal is considered cheaper and can be carried out continuously because the raw material comes from renewable wood. Wood charcoal has several advantages, including relatively cheap price, easy to store and use, high fuel value and more efficient in transportation. The approach used in this program research is Asset Based Community Development (ABCD) approach. The purpose of this program research is as an effort to improve the community's economy through the development of a wood charcoal business in Ketandan Village. The results of the community service program were: First, Marketing of Local Wood Charcoal Products in Ketandan Village. Second, Utilization of Vacant Land. After the completion of the service program, the programs that have been implemented will be monitored by the community service team in Ketandan Village.